Enmity and violence in early modern Europe - Carroll, Stuart 1965- (Cambridge University Press, 2023)
In this original study Stuart Carroll transforms our understanding of Europe between 1500 and 1800 by exploring how ordinary people felt about their enemies and the violence it engendered. Enmity, a state or feeling of mutual opposition or hostility, became a major social problem during the transition to modernity. He examines how people used the law, and how they characterised their enmities and expressed their sense of justice or injustice. Through the examples of early modern Italy, Germany, France and England, we see when and why everyday animosities escalated and the attempts of the state to control and even exploit the violence that ensued. This book also examines the communal and religious pressures for peace, and how notions of good neighbourliness and civil order finally worked to underpin trust in the state. Ultimately, enmity is not a relic of the past; it remains one of the greatest challenges to contemporary liberal democracy.